MEMBACA KEMUNGKINAN FILM SEBAGAI OBJEK PENELITIAN SASTRA - Tri Wahyudi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. There is still a debate on film and literature relationship. Some argued that films and videos were in the opposite site of language activities, that is, films and videos tried to present the concrete, particular, and sensational forms of life. While others argued that films might be the objects of literary researches. This article aims at exploring the relationship of films and literature and uncovering the position of films as the object of research of literature students. Films and literatue’s relationship cannot be separated from the activity of adapting literary work into movie, or ecranisation. Ecranisation theory bridges the relationship of film and literature and make a film suitable object of a literary research. Yet, there are some who argue that a film which is not the product of ecranisation can become the object of a literary research under the umbrella of culture study, that everything may undergo a redefinition. Key words: literature, film, ecranisation, text, redefinition